DO WE DREAM UNDER THE SAME SKY. - Tiravanija, Rirkrit; Hirsch, Nikolaus; Melasniemi, Antto; Müller, Michel (Berlin : Sternberg Press, 2015)
Tiravanija, Rirkrit ; Hirsch, Nikolaus ; Melasniemi, Antto ; Müller, Michel
Published in conjunction with the eponymous installation at Art Basel 2015, DO WE DREAM UNDER THE SAME SKY is an extension of the collaboration between artist Rirkrit Tiravanija, architects Nikolaus Hirsch and Michel Müller, and chef Antto Melasniemi. Designed by Hirsch and Müller as an outdoor shelter, the installation, made of modular bamboo and steel, welcomes visitors to engage in discussions while participating in the convivial atmosphere of shared food. This supplemental publication includes interviews, texts, images, and poems that illuminate the installation's properties of self-sufficiency and how it was conceived as a new component of Tiravanija and Kamin Lertchaiprasert's ongoing project “the land,” a self-sustaining artistic community near Chiang Mai, Thailand. At the end of the festival, the structure will be transported to Thailand and will be the first building block of a new workshop on the land. (provided by publisher)
DO WE DREAM UNDER THE SAME SKY, Art Basel, Basel, 2015
boek